Decentralisation of Active Labour Market Policy: The Case of Swedish Local Employment Service Committees - Per Skedinger; Martin Lundin (The Research Institute of Industrial Economics (IUI), 2000)
Decentralisation of decision-making in active labour market policy makes it possible to use local information to the fullest, but may also impinge on the fulfilment of national objectives, as suggested by principal-agent theory. The purpose of this study is to ex-amine the effects of a Swedish pilot programme in 1996, which strengthened the role of the local authorities in labour market policy in parts of the country. Survey evidence suggests a non-negligible divergence between the objectives of the municipality repre-sentatives and the central government's goals. Regarding programme effects, our econometric findings do not indicate any increase in geographical lock-in of the unem-ployed, but decentralisation seems to spur local initiatives in the form of labour market programmes organised by the municipalities. In addition, targeting on outsiders is to some extent more common in municipal projects than in others.
Keywords: H70; J60; 330; Active labour market policy; Decentralisation; Intergovernmental relations; Arbeitsmarktpolitik; Dezentralisierung; Schweden